Pengembangan Modul Praktikum Kimia Berbasis Problem Based Learning (PBL) Pada Materi Larutan Elektrolit Dan Non Elektrolit - Jehadut, Robialdus; Tukan, Maria Benedikta; Komisia, Faderina (STKIP ROKANIA, 2023)
This research and development is motivated by the problem where teaching materials or practicum modules are not yet available and to do the practicum, work procedures must be written directly on the blackboard on the day of the practicum. For this reason, efforts are needed to solve this problem by integrating the practicum module with a problem based learning model on electrolyte and nonelectrolyte solutions. The aims of this study were (1) to determine the validity of the problem-based learning chemistry practicum module on electrolyte and nonelectrolyte solutions, (2) to determine the students' responses to the validity of the problem-based learning chemistry practicum module on electrolyte and nonelectrolyte solutions. The research design used is the ADDIE model which is limited to 3 stages, namely Analysis, Design, Development. The results of this study are (1) the validity of the practicum module obtained from the assessment of 2 material expert validators in the very appropriate category and the media expert validator in the very appropriate category, (2) The results of student responses to the problem based learning chemistry practicum module are in good category. with a percentage of 77.47%.